Environment on students’ mathematical representation abilities: A quantitative study in an Indonesian secondary school - Izzati, Nurma; Maula, Minhatul; Bilqisth, Lu’lu Qolbi (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
This quantitative study aims to examine the influence of the learning environment on students’ mathematical representation abilities. The research is motivated by the relatively low levels of mathematical representation skills observed among students, which may be associated with variations in the quality of their learning environments. The study was conducted at a junior high school in Cirebon during the 2024/2025 academic year, involving 30 students selected through purposive sampling. Data were collected using a questionnaire to measure students’ perceptions of the learning environment and a test instrument to assess their mathematical representation abilities, including verbal, visual, and symbolic representations. The findings indicate that the learning environment has a significant influence on students’ mathematical representation abilities. However, the results also reveal that both the quality of the learning environment and students’ mathematical representation abilities are relatively low. Statistical analysis shows that the learning environment accounts for 9.3% of the variance in students’ mathematical representation abilities, while the remaining 91.7% is explained by other factors beyond the learning environment. Future studies should explore the influence of additional factors such as learning motivation, instructional methods, and cognitive abilities on students’ mathematical representation skills. Moreover, research involving larger and more diverse populations is recommended to enhance the generalizability and applicability of the findings.